Literacy in Early Childhood with Hearing Loss: Challenges and Strategies in Education - Nur Latifah; S. Sumihatul Ummah MS; Petrus Jacob Pattiasina; Ida Bagus Made Wisnu Parta; Supriyanti (Journal of Childhood Development, 2023)
This research analyzes literacy development in children with hearing loss, focusing on the challenges faced and strategies used in the educational context. Literacy plays a vital role in learning and social integration, yet children with hearing loss may face barriers in developing these skills. Through interviews with notable education experts, parents and teachers, this study identifies specific literacy development patterns and uncovers the challenges faced. The results of this study are expected to provide a better understanding of literacy development in children with hearing loss and provide insights into the challenges and effective educational strategies. The implications of this study can contribute to the development of better inclusive curricula and the provision of appropriate support for children with hearing loss in developing their literacy skills.